1999
DOI: 10.1016/s0375-9601(99)00004-3
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Deuterium-tritium fusion reactors without external fusion breeding” by S. Eliezer et al. (Phys. Lett. A 243 (1998) 311)

Abstract: Inclusion of inverse Compton effects in the calculation of deuterium-deuterium burn under the extreme conditions considered by Eliezer et al. [Phys. Lett. A 243 (1998) 298] are shown to decrease the maximum burn temperature from about 300 keV to only 100-150 keV. This decrease is such that tritium breeding by the DD → T + p reaction is not sufficient to replace the small amount of tritium that is initially added to the deuterium plasma in order to trigger ignition at less than 10 keV.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…We find that the amount of tritium left in the pellet after the burn is significantly larger than that estimated earlier. Further, we observe that inverse Compton scattering, as incorporated by Gsponer and Hurni [14], has a lesser effect on tritium breeding. The organization of this paper is as follows.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…We find that the amount of tritium left in the pellet after the burn is significantly larger than that estimated earlier. Further, we observe that inverse Compton scattering, as incorporated by Gsponer and Hurni [14], has a lesser effect on tritium breeding. The organization of this paper is as follows.…”
Section: Introductionmentioning
confidence: 64%
“…The conditions necessary for realizing tritium breeding crucially depend on the energy deposition and loss rates from the plasma. Thus radiation losses due to inverse Compton scattering and photon losses have been shown to affect tritium breeding in a major way [14]. Therefore we re-evaluated different configurations with the improved model of charged particle and neutron energy deposition discussed above.…”
Section: Tritium Breedingmentioning
confidence: 99%
See 2 more Smart Citations
“…Another solution has been proposed to be adding a small amount of tritium to the deuterium fuel in the form of DT x , where x is the ratio of tritium to deuterium in initial fuel 18,19 . It has been shown that in x ∼ 0.01 and with a given initial condition, namely, density ρ 5000 g/cm 3 , areal density ρR 12.5 g/cm 2 , and temperature T 10 KeV , internal breeding of tritium takes place.…”
Section: Introductionmentioning
confidence: 99%